A feasibility and pilot randomized controlled trial of the "Timing it Right Stroke Family Support Program". (November 2015) - Cameron, Jill I; Naglie, Gary; Green, Theresa L; Gignac, Monique AM; Bayley, Mark; Huijbregts, Maria; Silver, Frank L; Czerwonka, Anna
Objective: Examine feasibility of conducting a randomized controlled trial of the Timing it Right Stroke Family Support Program (TIRSFSP) and collect pilot data. Design: Multi-site mixed method randomized controlled trial. Setting: Acute and community care in three Canadian cities. Subjects: Caregivers were family members or friends providing care to individuals who experienced their first stroke. Intervention: The TIRSFSP offered in two formats, self-directed by the caregiver or stroke support person-directed over time, were compared to standard care. Main measures: Caregivers completed baseline and follow-up measures 1, 3 and 6 months post-stroke including Centre for Epidemiological Studies Depression, Positive Affect, Social Support, and Mastery Scales. We completed in-depth qualitative interviews with caregivers and maintained intervention records describing support provided to each caregiver. Results: Thirty-one caregivers received standard care ( n =10), self-directed ( n =10), or stroke support person-directed ( n =11) interventions. We retained 77% of the sample through 6-months. Key areas of support derived from intervention records ( n =11) related to caregiver wellbeing, caregiving strategies, patient wellbeing, community re-integration, and service delivery. Compared to standard care, caregivers receiving the stroke support person-directed intervention reported improvements in perceived support (estimate 3.1, P =.04) and mastery (estimate .35, P =.06). Qualitative caregiver interviews ( n =19) reflected the complex interaction between caregiver needs, preferences and available options when reporting on level of satisfaction. Conclusions: Preliminary findings suggest the research design is feasible, caregivers' needs are complex, and the support intervention may enhance caregivers' perceived support and mastery. The intervention will be tested further in a large scale trial.